The effect of progressive decay on timber of Eucalyptus saligna Sm. and Acacia mollissima Willd used in the mines of the Witwatersrand, with particular reference to the effect of preservative treatment on changes in the physical, mechanical and chemical properties - Bowen, J. W (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1942.